2018
DOI: 10.1186/s12957-018-1441-3
|View full text |Cite
|
Sign up to set email alerts
|

Safflower polysaccharide inhibits the development of tongue squamous cell carcinoma

Abstract: BackgroundSafflower polysaccharide (SPS) is one of the most important active components of safflower (Carthamus tinctorius L.), which has been confirmed to have the immune-regulatory function and antitumor effect. This study aimed to explore the effects of safflower polysaccharide (SPS) on tongue squamous cell carcinoma (TSCC).MethodsHN-6 cells were treated with 5 μg/mL cisplatin and various concentrations of SPS (0, 0.02, 0.04, 0.08, 0.16, 0.32, 0.64, and 1.28 mg/mL), and cell proliferation was measured. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…reported the relative cell viability of HN6 cells was 53% after high-concentration sa ower polysaccharide treatment for 24 h, etc. [54][55][56][57] Additionally, drugs can obstruct the advancement of the tumor by inhibiting the migration and invasion of tumor cells. After 24 h, the UPM displayed a mere 11% cell migration rate, marking a 4.6-fold reduction compared to the control group and a 2.1-fold decrease compared to the USPBNPs.…”
Section: Discussionmentioning
confidence: 99%
“…reported the relative cell viability of HN6 cells was 53% after high-concentration sa ower polysaccharide treatment for 24 h, etc. [54][55][56][57] Additionally, drugs can obstruct the advancement of the tumor by inhibiting the migration and invasion of tumor cells. After 24 h, the UPM displayed a mere 11% cell migration rate, marking a 4.6-fold reduction compared to the control group and a 2.1-fold decrease compared to the USPBNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a general phenomenon in cytotoxicity evoked by antitumor drugs and it is an important mechanism involved in cell death, growth, invasion, and differentiation. Additionally, cell apoptosis is concerned with the malignant tumor progression 22 . Bcl-2 and Bax are commonly considered as important mediators of cell apoptosis and belong to Bcl-2 families 23 .…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of reports indicated that the activation of COX-2 in various types of tumors is related to the progression of the malignant tumor. Additionally, the COX-2 inhibitor could inhibit the growth of cancer cells and improve the antiangiogenic tumor therapy 22 . In our research, we observed that EGLP evoked apoptosis in HCT-116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that SPS could inhibit the proliferations of HN-6 human tongue squamous carcinoma cells and xenograft tumors in nude mice by inducing apoptosis and cell cycle arrest in the G0/G1 phase. The mechanism might be related to the fact that SPS regulates the mRNA and protein expression of cyclooxygenase-2 (down), Bcl-2 (down), Bax (up), and cleaved caspase-3 (up) in tumor cells (Zhou et al, 2018).…”
Section: Other Antitumor Activitiesmentioning
confidence: 99%